THE ADAPTIVE SYSTEM OF CAR TRAFFIC VOLUME ORGANIZATION - Doroshko, S. V. (Science and Transport Progress, 2010)
The adaptive system of the organisation of car traffic volumes, which in the conditions of non-uniformity of the traffic volume capacity and transport demand is one of measures of increasing the efficiency of transportations and acceleration of a car turn owing to the reduction of idle time of cars under accumulation and increase of level of the transit car traffic volume at technical stations is offered.